2020
DOI: 10.1016/j.kint.2019.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between the nervous system and the kidney

Abstract: Under physiological states, the nervous system and the kidneys communicate with each other to maintain normal body homeostasis. However, pathological states disrupt this interaction as seen in hypertension, and kidney damage can cause impaired renorenal reflex and sodium handling. In acute kidney injury (AKI) and chronic kidney disease (CKD), damaged kidneys can have a detrimental effect on the central nervous system. CKD is an independent risk factor for cerebrovascular disease and cognitive impairment, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 147 publications
0
65
0
1
Order By: Relevance
“…A single-center retrospective chart review had found that the mortality rate of patients with combined ECMO and CRRT was higher than that of those receiving ECMO alone (26). A number of studies have indicated that damaged kidneys could have a detrimental effect on the central nervous system in acute kidney injury (AKI), which was also found to be a risk factor for delirium and coma during critical illness (27)(28)(29). In the present study, the proportion of CRRT in the NC group (69.2%) was significantly higher than that in the nNC group (28.6%), and CRRT was one of the independent risk indicators for V-A ECMO patients with neurological complications.…”
Section: Discussionmentioning
confidence: 99%
“…A single-center retrospective chart review had found that the mortality rate of patients with combined ECMO and CRRT was higher than that of those receiving ECMO alone (26). A number of studies have indicated that damaged kidneys could have a detrimental effect on the central nervous system in acute kidney injury (AKI), which was also found to be a risk factor for delirium and coma during critical illness (27)(28)(29). In the present study, the proportion of CRRT in the NC group (69.2%) was significantly higher than that in the nNC group (28.6%), and CRRT was one of the independent risk indicators for V-A ECMO patients with neurological complications.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the study focused on the hippocampus, but effects on amygdala, insular and cingulate gyrus could be also possible as a background for the functional changes leading specifically to dementia. Moreover, an autonomic imbalance was suggested for the pathophysiology in CKD or AKI ( Tanaka and Okusa, 2020 ), so that an impact of uremic toxin exposure on the autonomic areas of the brain could be associated with this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased kidney function in patients with chronic kidney disease (CKD) or acute kidney injury (AKI) often leads to neurological effects such as cognitive impairment, neuropathy and cerebrovascular disease ( Tanaka and Okusa, 2020 ). Blood-borne toxins, normally eliminated by healthy kidneys, are thought to affect brain function through kidney-brain crosstalk ( Lu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The annual incidence of stroke is 15.1% in hemodialysis and 9.6% in CKD patients. In comparison the annual incidence of stroke is 2.6% in patients without CKD (18). Stroke rate in peritoneal dialysis patients is less well-characterized.…”
Section: Clinical Relationship Between Chronic Kidney Disease Stroke and Stroke Outcomesmentioning
confidence: 97%